Seroprevalance of Torch Infection in Pregnant Women in Basra City Southern of Iraq - Ali. F. Hussein (Journal of Global Pharma Technology, 2016)
Background torch infection (toxoplasma gondii, rubella virus, cytomegalovirus, herpes simplex virus) the causative agent for congenital infections in infants and abortion in pregnant women. Objectives the goal of the study was to determine the rates of infection of the toxoplasmosis and viruses that cause abortion in pregnant women. Methods kit (torch) igm, elisa technique. Result: a total of 50 serological samples were collected from adult pregnant women from 2018 -10 to 2018-oct-12. The number of qurna samples was 25 positive infection counts 15 and the estimated infection was 15/25 which accounted for 60%.while the infection rate in abi al-khasib district of the total 25 samples of the number of infection 8 and estimated the proportion of infection 8/25, which constitutes 32% of the toxoplasmosis. the results of the current epidemiological study confirmed that the viruses that cause abortion in the qurnah& abe al-khasib district of rubella were 4of the 50 blood samples (serum) showing that the percentage of infection is4/50, which is 8% and the rate of infection of cytomegalovirus 8/50 which is 16% the results showed that herpes virus was more infected than the virus above 24/50 and that the percentage was estimated to be 48%. these results indicate that the most common percentage among pregnant women toxoplasmosis& herpes virus cytomegalovirus, rubella).)60%, 48%, 16%, and 8%, respectively. The results have been confirmed by using a technique elisa. Conclusion: we concluded from the study the two most common cause's abortion in pregnant women in basra city southern of Iraq t gondi 60%, herpes virus 48%  Keywords: TORCHT- Toxoplasmosis, R –Rubella C- Cytomegalovirus. H- Herpes simplex virus.